Boundary value problem for the third-order equation with multiple characteristics - Atamuratovna, Djumaniyazova Khilola; Risbekovich, Khashimov Abdukomil (Annals of Mathematics and Physics, 2023)
The article constructs a unique solution to a tertiary-order equation with multiple characteristics with boundary conditions that include all possible local boundary conditions. The uniqueness of the solution of boundary value problems is proved by the method of integral equations using the sign-definiteness of quadratic forms. When proving the existence of a solution to the problem, Green's function method, the theory of integral equations and potentials are used.